Wilcox, Jonathan. 2023. Humour in Old English Literature: Communities of Laughter in Early Medieval England. Pp. vii + 343. ISBN 9781487545307. - Samantha Zacher (SELIM, 2025)
Book Review of Wilcox, Jonathan. 2023. Humour in Old English Literature: Communities of Laughter in Early Medieval England. Pp.  vii + 343. ISBN 9781487545307.